Nurse staffing and patient-perceived quality of nursing care: a cross-sectional analysis of survey and administrative data in German hospitals - Winter, Vera; Dietermann, Karina; Schneider, Udo; Schreyögg, Jonas (BMJ open, 2021)
ObjectiveTo examine the impact of nurse staffing on patient-perceived quality of nursing care. We differentiate nurse staffing levels and nursing skill mix as two facets of nurse staffing and use a multidimensional instrument for patient-perceived quality of nursing care. We investigate non-linear and interaction effects.SettingThe study setting was 3458 hospital units in 1017 hospitals in Germany.ParticipantsWe contacted 212 554 patients discharged from non-paediatric, non-intensive and non-psychiatric hospital units who stayed at least two nights in the hospital between January and October 2019. Of those, 30 174 responded, yielding a response rate of 14.2%. Our sample included only those patients. After excluding extreme values for our nurse staffing variables and removing observations with missing values, our final sample comprised 28 136 patients ranging from 18 to 97 years of age (average: 61.12 years) who had been discharged from 3458 distinct hospital units in 1017 hospitals.Primary and secondary outcome measuresPatient-perceived quality of nursing care (general nursing care, guidance provided by nurses, and patient loyalty to the hospital).ResultsFor all three dimensions of patient-perceived quality of nursing care, we found that they significantly decreased as (1) nurse staffing levels decreased (with decreasing marginal effects) and (2) the proportion of assistant nurses in a hospital unit increased. The association between nurse staffing levels and quality of nursing care was more pronounced among patients who were less clinically complex, were admitted to smaller hospitals or were admitted to medical units.ConclusionsOur results indicate that, in addition to nurse staffing levels, nursing skill mix is crucial for providing the best possible quality of nursing care from the patient perspective and both should be considered when designing policies such as minimum staffing regulations to improve the quality of nursing care in hospitals.